Graphene-assisted construction of electrocatalysts for carbon dioxide reduction - Hu, Huawen; Ou, Jian Zhen; Xu, Xuejun; Lin, Yinlei; Zhang, Yuyuan; Zhao, Hong; Chen, Dongchu; He, Minghui; Huang, Yugang; Deng, Lifang (Chemical engineering journal (Lausanne, Switzerland : 1996), 2021)
•Review of graphene-assisted construction strategies of both metal and non-metal based electrocatalysts.•Discussion of CO2RR electrocatalytic performances of various graphene − metal composites.•Overview of enhancement approaches of the graphene-based non-metal CO2RR catalytic activities.•Challenges and perspectives for the future development of graphene-based CO2RR electrocatalysts. The electrochemical conversion of the greenhouse gas, carbon dioxide (CO2), to energy fuels and value-added chemicals presents one of the most valuable approaches to harvest pollutants and produce renewable energy. However, the stable molecular structure of CO2 and the sluggish reaction kinetics make CO2 reduction reaction (CO2RR) formidably challenging to achieve reaction rate and selectivity practical in industry. Graphene and its derivatives have been considered a group of intriguing materials to develop advanced CO2RR electrocatalysts due to their large specific surface area, remarkable electron transfer ability, superior stability, and easy tunability of the structure and surface properties. Herein, we comprehensively discuss the state-of-the-art electrocatalysts constructed with graphene and derivatives for active and selective CO2RR within the recent five years, mainly including the electrocatalysts with both metal-based (e.g., noble, non-noble, or combined thereof) and non-metal (e.g., doped, modified, defected, or composited) catalytic sites. To present the versatile, high-performance metal-based CO2RR electrocatalysts constructed with graphene, we further subdivide them according to the sizes, oxidation states, metal species synergies, dimensionalities, and versatility. Finally, we provide the challenges and perspectives in this emerging area of utilising CO2 to produce various carbon-based fuels and chemicals via graphene chemistry.